Experimental Research on Modification of Mechanical Properties Values for Heat Treated Welded Joints - Marian-Iulian NEACȘU (The Annals of “Dunarea de Jos” University of Galati. Fascicle IX, Metallurgy and Materials Science)
This paper presents the results of studies and research on the values of the mechanical properties of welded joints on OLC 20 and OLC 25 steel samples, in the case that no heat treatment is performed on them and in several cases when the samples are heat treated after welding. After welding and heat treatments for normalization, hardening and tempering was carried out on the samples. After performing the heat treatments, the researched samples were subjected to tests to determine: Vickers hardness, mechanical resistance Rm and breaking energy KV. Analysing the obtained results, it can be concluded that following the thermal normalization treatment, the optimal complex of the values of the studied mechanical properties was obtained.